2015
DOI: 10.1111/avj.12351
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of the bioavailability and efficacy of orally administered flunixin, carprofen and ketoprofen in a pain model in sheep

Abstract: The three NSAIDs reached inferred therapeutic concentrations in blood at 2 h after oral administration. The oil of turpentine lameness model may need further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
0
9
3
Order By: Relevance
“…Concentrations measured in this study were somewhat lower compared with those reported in our previous study (Marini et al, 2015) where flunixin concentration in plasma reached values between 2.6 -4.1 µg/mL 2 h after a single oral dose (4 mg/kg) in sheep. Reports of therapeutic concentrations of flunixin in farm animals are limited, however, Toutain et al, (1994) reported therapeutic effects in horses when plasma concentrations reached 0.2 -0.9 µg/mL.…”
Section: Discussioncontrasting
confidence: 91%
“…Concentrations measured in this study were somewhat lower compared with those reported in our previous study (Marini et al, 2015) where flunixin concentration in plasma reached values between 2.6 -4.1 µg/mL 2 h after a single oral dose (4 mg/kg) in sheep. Reports of therapeutic concentrations of flunixin in farm animals are limited, however, Toutain et al, (1994) reported therapeutic effects in horses when plasma concentrations reached 0.2 -0.9 µg/mL.…”
Section: Discussioncontrasting
confidence: 91%
“…When consuming feed ad-libitum, the majority of sheep (7 out of 8) achieved plasma flunixin concentrations above 1.0 µg/mL within 2 h of consuming medicated feed, with maximum concentrations (between 1.33 and 2.80 µg/mL) being reached on average by 6 h. Concentrations observed in this current study were somewhat less to those reported in our previous study (Marini et al 2015) where flunixin concentration in plasma reached between 2.6 -4.1 µg/mL 2 h after a single oral dose (4mg/kg) in sheep. Reports of therapeutic concentrations of flunixin in farm animals are limited, however, Toutain et al (1994) reported therapeutic effects in horses when plasma concentrations reached 0.2-0.9 µg/mL.…”
Section: Discussioncontrasting
confidence: 92%
“…A randomised trial looks at the bioavailability and efficacy of flunixin, carprofen and ketoprofen in a model of pain in sheep . Although there is little data on the use of NSAIDs in sheep, if these anti‐inflammatories could be given orally and incorporated into feed, they could be used by producers.…”
Section: Production Animalsmentioning
confidence: 99%